What If Educational Inquiry Were Neither a Social Science Nor a Humanities Field? Revisiting Joseph Schawb’s “The Practical” in the Aftermath of the Science Wars - Donmoyer, Robert (Education Policy Analysis Archives, 2014)
The recent debates about what constitutes scientific research in Education, on the one hand, and the so-called “paradigm wars” that got played out in the final quarter of the 20th century, on the other, are more similar than different. At the center of both controversies was the relative worth of quantitative and qualitative research methods. Both controversies also distracted researchers’ from addressing the substantive problems that plague schools and other educational organizations. This paper attempts to move the field beyond the debates of the past and similar debates that seem likely to occur in the future. Inspired, in large part, by Joseph Schwab’s largely unheeded critique of the curriculum field in the late 1960s and early ‘70s, the paper attempts to re-conceptualize what inquiry in a field like Education should look like, as well as the role that quantitative, qualitative, and mixed-methods research could play in a re-conceptualized approach to inquiry.